2021
DOI: 10.2147/ndt.s340189
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Better Than High-Sensitivity C-Reactive Protein in Predicting Stroke-Associated Pneumonia in Afebrile Patients

Abstract: Purpose To evaluate the association between neutrophil-to-lymphocyte ratio (NLR) and stroke-associated pneumonia (SAP) in patients with acute ischemic stroke (AIS) without fever and to clarify whether NLR has an advantage over high-sensitivity C-reactive protein (hs-CRP) in predicting SAP. Patients and Methods A total of 434 patients with AIS without fever were assessed in this study. Multivariable analysis was used to evaluate the relationship between NLR and SAP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Studies have shown that high NLR, with cutoff values ranging from 2.44 to 3.75, is significantly associated with stroke-associated pneumonia [8,9,17,18]. Similarly, as shown in this study, patients with high NLR (≥2.72) were more likely to have pneumonia during the hospitalization for stroke than those with low NLR (9.1% vs. 6.3%, p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown that high NLR, with cutoff values ranging from 2.44 to 3.75, is significantly associated with stroke-associated pneumonia [8,9,17,18]. Similarly, as shown in this study, patients with high NLR (≥2.72) were more likely to have pneumonia during the hospitalization for stroke than those with low NLR (9.1% vs. 6.3%, p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Endothelial cells are also damaged in patients with stroke, leading to platelet activation, the expression of adhesion molecules, and the release of inflammatory factors, resulting in atherosclerosis, thrombosis, and a decrease in platelet count (McMorran et al., 2009 ; Modjeski & Morrell, 2014 ). In addition, it has been shown that T‐lymphocytes and neutrophil‐to‐lymphocyte ratio have been shown to predict SAP development (Feng et al., 2018 ; Wu, Zhang et al., 2021 ). However, SII provides a more stable and objective response to changes in neutrophil, lymphocyte, and platelet counts in patients with stroke and can be used to predict SAP.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to high-sensitivity C-reactive protein, NLR is strongly associated with the occurrence of stroke-associated pneumonia. 16 Hu et al 17 reported that NLR is associated with 90-day poor outcomes in stroke patients, however, the AUC of high NLR was insufficiently high to predict the poor outcome. In contrast, the AUC of NLR (0.717) in the present study had a good predictive value.…”
Section: Discussionmentioning
confidence: 99%